2010
DOI: 10.1097/brs.0b013e3181c20fb5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevention of Intervertebral Cage Overhang With Minimally Invasive Lateral Approach Fusions

Abstract: The risk of placing an excessively long cage, when the insertion site is located in the anterior 1/3 of the disc, is relatively high, when performing MIS lateral approach interbody fusions. When using an anterior entry point for the insertion of the cage, choosing a 15% shorter cage length compared with that measured on the AP should prevent anterolateral protrusion of the cage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Both patients' neurologic deficits resolved after reoperation. A radiologic study by Regev et al 34 The XLIF is a formidable technique to achieve an indirect decompression and stabilization and in our experience a direct decompression may be unnecessary. Pimenta et al showed a 30% and 50% increase in central canal area and foraminal height respectively with XLIF.…”
Section: Discussionmentioning
confidence: 66%
“…Both patients' neurologic deficits resolved after reoperation. A radiologic study by Regev et al 34 The XLIF is a formidable technique to achieve an indirect decompression and stabilization and in our experience a direct decompression may be unnecessary. Pimenta et al showed a 30% and 50% increase in central canal area and foraminal height respectively with XLIF.…”
Section: Discussionmentioning
confidence: 66%
“…In the emergency department, opioids are among the most commonly used agents (61.7%) followed by NSAIDs (49.5%) for LBP. The most commonly used combination is NSAIDs with skeletal muscle relaxants (26.2%), as seen in our case, followed by NSAIDs with opioids (25.9%) [9]. Adequate immediate pain relief has been reported with steroids and local anesthetic infiltration of anomalous lumbosacral articulations in eight out of 10 patients, but only one patient remained pain-free after two years [9].…”
Section: Discussionmentioning
confidence: 79%
“…The most commonly used combination is NSAIDs with skeletal muscle relaxants (26.2%), as seen in our case, followed by NSAIDs with opioids (25.9%) [9]. Adequate immediate pain relief has been reported with steroids and local anesthetic infiltration of anomalous lumbosacral articulations in eight out of 10 patients, but only one patient remained pain-free after two years [9]. For patients with BS who fail to respond to conservative management, surgical excision of the anomalous joint is indicated.…”
Section: Discussionmentioning
confidence: 84%
“…[26][27][28][29][30][31][32][33] There have already been various anatomical descriptions of the retroperitoneum, the psoas, and the lumbar plexus. [34][35][36][37][38][39] Rodgers et al 40 reported initial results in 100 patients who underwent XLIF for multiple degenerative conditions in 2007. He described the procedure as safe and reproducible, with a low rate of complications (2%), few days in hospital (average of 1.5 days), and good improvement of the VAS (68.7%).…”
Section: Discussionmentioning
confidence: 99%